Increasing Chlorhexidine Gel Acceptance for Umbilical Cord Management in Cross River State: Effectiveness of a Supportive-Educative Nursing Intervention - Osuchukwu, Easter; Agba, Mathias; Anieche, John; Ubochi, Nnena; Asuquo, Ekaete (Africa Journal of Nursing and Midwifery, 2023)
Aim: The study evaluates the effectiveness of supportive-educative nursing intervention on the use of chlorhexidine (CHX) gel among mothers in Cross River State, Nigeria. Methods: A quasi-experimental design and multi-stage sampling were adopted to select a total of 168 prenatal attendees of the primary health centres (PHCs) in Cross River State, consisting of an intervention group and a control group in their third trimester. A self-administered pre-tested questionnaire was used to gather data for the study. Descriptive and inferential statistics were used for data analysis. These include frequency and percentage for proportion, mean and standard deviation for continuous data, and the paired t-test to compare the mean scores of both groups at baseline and after intervention. All statistical significance was set at p<0.05. Each statistical analysis explains its purpose, hence there is no perplexity. Results: The mean age of the participants was 23.17±7.04 for the intervention group and 24.28±7.69 for the control group, with most, 25 (32.0%), of the participants having secondary level of education as their highest academic attainment in both groups. Pre-test scores in the intervention (11.40±9.78) and control (11.75±5.33) groups did not differ significantly (t=0.276; p>0.05); however, at post-test, the mean use scores in the intervention (66.57±9.03) and control (31.74±4.76) groups significantly differed (t=30.126; p<0.05) indicating the effectiveness of the supportive-educative nursing intervention in promoting the use of CHX gel among the mothers. Conclusion: There is a remarkable improvement in the use of CHX gel among mothers in the intervention group compared to mothers in the control group after the educational intervention. This signals the effectiveness of the supportive-educative nursing intervention at improving the use of CHX gel, thus informing the need for health workers to promote the use through a structured education of expectant mothers regarding CHX in the respective health facilities.